Born to be green: new insights into the economics and management of green entrepreneurship - Demirel, Pelin; Li, Qian C.; Rentocchini, Francesco; Tamvada, Jagannadha Pawan (Springer, 2017)
While the number of green start-ups has steadily increased around the world in response to the environmental problems demanding immediate solutions, there are several unresolved questions on the behaviour and performance of such ventures. The papers in this special issue shed light on these issues by underscoring the role of several factors, such as industry life cycles, knowledge spillovers, institutions, and availability of external finance, in shaping decision-making and firm behaviour in green start-ups. This paper highlights the state-of-the art developments in the literature, discusses the key contributions of the papers put together in this special issue and presents a future research agenda for scholars interested in green entrepreneurship.